Setting up a clinical trial for a novel disease: a case study of the Doxycycline for the Treatment of Nodding Syndrome Trial - challenges, enablers and lessons learned - Ronald Anguzu; Pamela R Akun; Rodney Ogwang; Abdul Rahman Shour; Rogers Sekibira; Albert Ningwa; Phellister Nakamya; Catherine Abbo; Amos D Mwaka; Bernard Opar; Richard Idro (Taylor & Francis Group, 2018)
A large amount of preparation goes into setting up trials. Different challenges and lessons are experienced. Our trial, testing a treatment for nodding syndrome, an acquired neurological disorder of unknown cause affecting thousands of children in Eastern Africa, provides a unique case study. As part of a study to determine the aetiology, understand pathogenesis and develop specific treatment, we set up a clinical trial in a remote district hospital in Uganda. This paper describes our experiences and documents supportive structures (enablers), challenges faced and lessons learned during set-up of the trial. Protocol development started in September 2015 with phased recruitment of a critical study team. The team spent 12 months preparing trial documents, procurement and training on procedures. Potential recruitment sites were pre-visited, and district and local leaders met as key stakeholders. Key enablers were supportive local leadership and investment by the district and Ministry of Health. The main challenges were community fears about nodding syndrome, adverse experiences of the community during previous research and political involvement. Other challenges included the number and delays in protocol approvals and lengthy procurement processes. This hard-to-reach area has frequent power and Internet fluctuations, which may affect cold chains for study samples, communication and data management. These concerns decreased with a pilot community engagement programme. Experiences and lessons learnt can reduce the duration of processes involved in trial-site set-up. A programme of community engagement and local leader involvement may be key to the success of a trial and in reducing community opposition towards participation in research.